Computer-assisted Writing of Medical Reports — A Bibliography - Köhler, C. O.; Wagner, G.; Wolber, U. (Methods of Information in Medicine, 1979)
Since the middle of the sixties, the possibilities of electronic data processing have been used to an increasing extent not only for internal communication in the hospital itself but also for external communication between hospital, medical practitioners, health offices etc. The problems arising when writing a medical report or an epicrisis are very similar so that we considered both aspects of the problem of automating the setting up of reports in this bibliography.We are not conceited enough to believe that we have covered all relevant papers concerning this widely dispersed subject. Surely, however, this bibliography will offer a good approach to special studies. We should appreciate advice about missing references.